Information management in times of crisis - Haelim Park Anderson; Adam Copeland (Federal Reserve Bank of New York, 2019)
How does information management and control affect bank stability? Following a national bank holiday in 1933, New York state bank regulators suspended the publication of balance sheets of state-charter banks for two years, whereas the national-charter bank regulator did not. We use this divergence in policies to examine how the suspension of bank-specific information affected depositors. We find that state-charter banks experienced significantly less deposit outflows than national-charter banks in 1933. However, the behavior of bank deposits across both types of banks converged in 1934 after the introduction of federal deposit insurance.
Keywords: G21; G28; N22; 330; information management; bank opacity; banking crisis; Great Depression; depositor confidence